Investigation of Anxiety, Depression, Sleep, and Family Function in Caregivers of Children With Epilepsy - Zhang, Meiyan; Zhang, Huiting; Hu, Shuxian; Zhang, Man; Fang, Yu; Hu, Junjie; Liao, Jianxiang (Frontiers in Neurology, 2021)
Objective: Epilepsy is a chronic disease that places a heavy burden on caregivers. Previous studies have shown that caregivers of epilepsy patients often experience anxiety and depression, however few comprehensive studies have assessed their sleep quality and family function. Based on the current understanding of the anxiety and depression state of caregivers in children with epilepsy, we further explored the caregivers' sleep and family function and evaluated the predictors of the depression state of caregivers. Method: In this cross-sectional online anonymous survey, we sent an online questionnaire to the caregivers of children with epilepsy who visited our hospital. The QR code of the questionnaire was scanned at the follow-up course to conduct an online survey. The questionnaire contained questions about socio-demographic and clinical information, the Self-rating anxiety scale, Self-rating depression scale, Pittsburgh sleep quality index, and the Family assessment device. Result: A total of 308 caregivers of children with epilepsy aged 0-12 years were included in this study. The mean age of children with epilepsy was 4.8 ±3.18 years, and the average illness duration was 34.2 ±29.18 months.We found that 65.6% of the caregivers were in depression status, 41.9% were in anxiety status, and 49.0% had poor sleep quality. The proportion of unhealthy family functioning in each subscale was 45.1-96.1%, and the unhealthy behavior control function accounted for 96.1%. Binary Logistic regression analysis of the data showed that without co-caregivers (Odds ratio[OR], 5.193), free of anxiety status (OR,0.063), good sleep quality (OR,0.446), healthy family roles dimension (OR,0.344), and healthy family general functional dimension(OR,0.259) were predictors of depression status in caregivers of children with epilepsy. Conclusion: Anxiety and depression status are common in caregivers of children with epilepsy, with depression status being more prominent. Moreover, a considerable proportion of caregivers had poor sleep quality and unhealthy family function. The caregivers' anxiety status, sleep quality, family roles dimension, family general function dimension, and the number of co-caregivers were predictors of depression status in caregivers. In clinical practice, caregivers' anxiety and depression status, poor sleep quality, and unhealthy family functioning should be addressed along with the treatment of children with epilepsy.